ITN - Infrastructure, Telematics, & Navigation (GEOmedia, 2010)
ITN - Infrastructure, Telematics & NavigationSecond edition of ITN ended with over three thousand visitors. ITN is the first and only event in Europe that has managed to achieve the meeting of mobile information and intelligent infrastructure. The event in Turin managed to capture the attention of an international public companies, public administrators, managers of road and rail networks, researchers and media, and if, in addition to European countries, have confirmed attendance from Eastern countries and India, for the first time there were from Africa, demonstrating that the fund dell'Intellligent Trasport System is growing.